Kreativitas Guru dalam Meningkatkan Interaksi Siswa Melalui Pembelajaran Bermain di TK Lukman Al Hakim - Ai Siska Silvia; Dela Zahara (Edu Happiness : Jurnal Ilmiah Perkembangan Anak Usia Dini, 2024)
This research aims to find out how teacher creativity increases student interaction through play learning at Lukman Al Hakim Kindergarten. This research applies a qualitative approach with a case study method, namely a descriptive approach that allows a holistic understanding of learning problems at Lukman Al Hakim Kindergarten. Data collection was carried out through observation, interviews and documentation studies. The results of the research show that the method of learning while playing, especially using the snake and ladder game media, is able to increase interaction and relationships between students. In contrast to other methods, researchers noted the lack of interaction among Lukman Al Hakim Kindergarten students, which was influenced by their individualistic attitudes. So this learning method using snakes and ladders media can be an alternative learning media that is quite effective in implementing Lukman Al Hakim Kindergarten.